Superior vena cava obstruction following pericardial effusion absorption in the presence of a pericardial teratoma: a case report - Kai Guo; Hui Wang (Journal of Cardiothoracic Surgery)
Abstract Intrapericardial teratoma is a rare tumor that usually presents in neonates or during infancy because of the associated high degree of pericardial effusion, cardiac compression and severe respiratory distress. In this paper, we report a rare case of intrapericardial teratoma that was incidentally discovered in an infant with superior vena cava obstruction following pericardial effusion absorption. Echocardiography and thoracic computed tomography angiography revealed that the intrapericardial mass obviously suppressed the superior vena cava. The tumor was resected surgically. Histopathological examination confirmed the diagnosis of mature teratoma.